COVID-19 Exanthem vs. Drug Induced Maculopapular Rash in A Pediatric Patient: Diagnostic Challenge and Management Strategy - Anum, Qaira; Sugiharto, Audi (Journal of Pakistan Association of Dermatologists, 2023)
Introduction: Exanthem is a diffuse erythematous maculopapular skin eruption secondary to various conditions. Coronavirus disease-2019 (COVID-19) infections may manifest as maculopapular exanthem. A maculopapular rash can also be induced by medications. The distinction between viral exanthem and drug eruption may be challenging. Case report: A 4-month-old male infant was admitted in the pediatric department of a tertiary hospital in West Sumatera, Indonesia with diagnosis of post-craniotomy of cerebral abscess and a history of seizures. During admission, patient was consulted to the department of dermatology and venereology due to erythematous macules and papules of the face, trunk, upper and lower extremities without preceding prodromal symptoms. The patient was confirmed positive for COVID-19, almost concurrently with the eruption of maculopapular rash. Patient also get medications which of the drugs were high risk to induce allergic drug eruption, i.e antibiotics and anticonvulsants. Patient was observed strictly during the administration of those essential drugs with desensitization method. Repetition of nasopharyngeal PCR swab after 2 weeks showed negative conversion, along with the recovery of maculopapular exanthem. Discussion: Ascertaining a diagnosis of maculopapular exanthem caused can be established through anamnesis, prodromal symptoms, and appearance of cutaneous eruptions. However atypical symptoms often complicate the diagnosis. Dermoscopic, laboratory or histopathological examinations are not specific to rule out differential diagnoses. It has even been reported that viral infections and drugs can elicit cross-reactions that provoke maculopapular exanthem. Conclusion: â€œThreating throughâ€ combined with â€œWait and Observeâ€ methods can be considered in patients with maculopapular exanthem induced by COVID-19 and drugs. Keywords: Hypesensitivity reaction, SARS-Cov-2, Viral exanthem